2009
DOI: 10.1021/cg8004272
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Biomineralization: The Effect of Solution Composition on Coccolith Polysaccharide Functionality

Abstract: The calcite shields produced by unicellular marine algae demonstrate the remarkable crystal control that organisms can achieve through biomineralization. Emiliania huxleyi produces complex polysaccharides ("coccolith associated polysaccharides", CAP) that regulate crystal morphology by preferentially attaching to calcite acute step edges, thus promoting growth of the specific crystal faces required for design of that species of coccolith. However, to control crystal growth, the alga must be able to control CAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 31 publications
3
38
0
Order By: Relevance
“…This would, however, require that both of these contaminant phases be relatively uniformly distributed through the placoliths, in order to generate stable SIMS analyses through 20 cycles, and that both the organic contamination in the modern specimens, and diagenetic calcite overgrowth in fossil material, be of a similar magnitude. This is possible, if Mg is concentrated not in coccolith calcite but in polysaccharide coatings on the surfaces of coccolith crystal faces (Young et al, 1999;Young and Henriksen, 2003;Henriksen and Stipp, 2009). This could potentially contribute to increased Mg/Ca ratios in modern coccolith specimens not subject to oxidative/reductive cleaning and, feasibly, could contribute to pervasive nanometre-scale, Mg-rich diagenetic overgrowth phases on crystal surfaces throughout the coccolith structure.…”
Section: Effects Of Variable Preservation On Coccolith Trace Metal Comentioning
confidence: 99%
See 1 more Smart Citation
“…This would, however, require that both of these contaminant phases be relatively uniformly distributed through the placoliths, in order to generate stable SIMS analyses through 20 cycles, and that both the organic contamination in the modern specimens, and diagenetic calcite overgrowth in fossil material, be of a similar magnitude. This is possible, if Mg is concentrated not in coccolith calcite but in polysaccharide coatings on the surfaces of coccolith crystal faces (Young et al, 1999;Young and Henriksen, 2003;Henriksen and Stipp, 2009). This could potentially contribute to increased Mg/Ca ratios in modern coccolith specimens not subject to oxidative/reductive cleaning and, feasibly, could contribute to pervasive nanometre-scale, Mg-rich diagenetic overgrowth phases on crystal surfaces throughout the coccolith structure.…”
Section: Effects Of Variable Preservation On Coccolith Trace Metal Comentioning
confidence: 99%
“…Despite individual coccoliths ($3-15 lm) being one to two orders of magnitude smaller than planktonic foraminifera ($200-600 lm) (Schmidt et al, 2006), coccoliths are considerably more resistant to sub-lysocline dissolution than planktic foraminifera (Broecker and Clark, 2009). The relative resistance of coccolith carbonate to dissolution (Adelseck, 1973;Hover et al, 2001) reflects the underlying differences in the biomineralisation pathways of coccoliths and foraminifera (Young and Henriksen, 2003;Young et al, 2004;Bentov et al, 2009;Henriksen and Stipp, 2009). There are two major differences in biomineralisation between these groups, with key implications: first the size of individual calcite crystals in typical heterococcoliths, are on the order of 1 lm (Bown et al, 2008;Henriksen and Stipp, 2009), which is an order of magnitude larger than corresponding crystallites in planktonic foraminifera tests (on the order of 0.1 lm e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Henriksen and Stipp (2009) demonstrated that the capability of CAPs to bind onto calcite crystals depends on the ion composition of the solution in which CAPs are dissolved. A change of the ion composition inside the CV may therefore disturb controlled crystal growth.…”
Section: Cause Of Malformationsmentioning
confidence: 99%
“…11 Previous research by our group investigated the behaviour of coccolith associated polysaccharides that were extracted from cultured species and found that the adsorption activity of the macromolecules was largely a result of their OH functional groups. [12][13][14][15][16] The simplest inorganic molecule with an OH group is water and the simplest organic chain molecule is ethanol, where one end is OH and the other, CH 3 . Investigation of systems containing calcite-water-ethanol provided new insights into the strength of bonding of simple OH compounds.…”
Section: Introductionmentioning
confidence: 99%